On the biting activities of some anthropophilic Amazonian Simuliidae (Diptera) - Lacey, Lawrence A.; Charlwood, J. D. (Bulletin of Entomological Research, 1980)
Quantitative observations on the biting activities of Simulium simplicicolor Lutz and S. sanguineum Knab s.1. at Aripuanã, Mato Grosso, Brazil, and S. guianense Wise and S. sanguineum s.1. at Uru´, Par´, were made during the wet and dry seasons between June 1978 and August 1979. The species demonstrated characteristic attacking patterns regardless of abundance or environmental conditions. S. simplicicolorS. guianense and S. sanguineum s.1. at Uruá demonstrated bimodal biting patterns with early morning and late afternoon peaks. S. sanguineum s.1. at Aripuanã, however, bit throughout the day with three peaks of activity. Evidence is presented for circadian control of the biting patterns which are subject to modification by exogenous factors outside of an optimal range. S. simplicicolor seemed to be most affected by light intensity, whereas the other species were affected by variable combinations of light, temperature and humidity depending on the species and population. Physiological age sometimes also modified biting activity in S. simplicicolor. This variable was not studied in the other species. S. simplicicolor and S. guianense preferred biting man on the legs and S. sanguineum s.1. at Uruá preferred the upper torso, but S. sanguineum s.1. at. Aripuanã did not demonstrate a consistent preference for sites above or below the waist. Average engorgement times for all of the populations except the Uruá population of S. sanguineum s.1. were between 4·3 and 5·3 min. © 1980, Cambridge University Press. All rights reserved.